Development of a railway wagon-track interaction model: Case studies on excited tracks. (1st February 2018) - Xu, Lei; Chen, Xianmai; Li, Xuwei; He, Xianglin
Highlights: A theoretical framework used to characterize the wagon-track interactions is proposed and validated. A energy-variational principle is introduced to illustrate linear properties. The amplitude and frequency of track irregularity contribute to the derailments. This model can reveal the derailment process subject to large track irregularities. Large wheel-rail separations are located by time-frequency analysis method. Abstract: In this paper, a theoretical framework for modeling the railway wagon-ballast track interactions is presented, in which the dynamic equations of motion of wagon-track systems are constructed by effectively coupling the linear and nonlinear dynamic characteristics of system components. For the linear components, the energy-variational principle is directly used to derive their dynamic matrices, while for the nonlinear components, the dynamic equilibrium method is implemented to deduce the load vectors, based on which a novel railway wagon-ballast track interaction model is developed, and being validated by comparing with the experimental data measured from a heavy haul railway and another advanced model. With this study, extensive contributions in figuring out the critical speed of instability, limits and localizations of track irregularities over derailment accidents are presented by effectively integrating the dynamic simulation model, the track irregularity probabilistic model and time-frequency analysis method. The proposed approaches can provide crucial information to guarantee the running safety and stability of the wagon-track system when considering track geometries and various running speeds.